Novel Catalysts Derived From Carbazole; Characterization, Spectral, Catalytic Features, Examination of Thermal Behaviour and DNA Binding Studies - Bal, Selma (Fırat University, 2026)
By using N-ethylcarbazole and an aromatic primer amine, a schiff base ligand and its three metal complexes have been synthesized through imine condensation reaction. The structures of all the synthesized compounds have been proposed on the basis of various spectral analyses like nuclear magnetic resonance, infrared and mass spectroscopy techniques. All the synthesized compounds have been searched for their catalytic activities on the oxidation reactions of cyclohexene and styrene. The results of these experiments revealed quite good activities of the complexes as catalysts. DNA binding studies were also carried out on all the synthesized compounds by using UV-Vis spectroscopic measurements and all the coordiation compounds revealed much better binding konstants than the ligand itself. Finally the thermal features of all the compounds were reported with this paper

N-Ethylcarbazole ve bir aromatik primer amin kullanılarak imin kondenzasyon reaksiyonu üzerinden bir Schiff bazı ligantı ile üç metal kompleksi sentezlenmiştir. Sentezlenen tüm bileşikler Nükleer Manyetik Rezonans, Infrared, Mass Spektroskopi gibi birçok spektroskopik yöntem kullanılarak karakterize edilmiştir. Karakterize edilen tüm bileşiklerin katalitik aktiviteleri stiren ve siklohekzen’in oksidasyon reaksiyonları üzerinde ölçülmüştür. Bu deneyler elde edilen komplekslerin katalitik aktivitelerinin oldukça iyi olduğunu kanıtlamıştır. UV-Vis spektroskopik tekniği kullanılarak tüm bileşiklerin DNA bağlanma özellikleri incelenmiş olup koordinasyon bileşiklerinin sentezlenen ligant’tan daha iyi bağlanma sabitleri verdiği görülmüştür özellikle de Nikel komplex DNA’ya en güçlü bağlanma eğilimi göstermiştir. Son olarak tüm bileşiklerin termal özellikleri bu çalışma ile rapor edilmiştir.
Karbazolden Türemiş Yeni Katalizörler; Karakterizasyon, Spektral, Katalitik Özellikler, Termal Davranışlarının İncelenmesi ve DNA Bağlanma Çalışmaları
Keywords: Main Group Metal Chemistry; Ana Grup Metal Kimyası